O direito à televisitação dos pacientes internados: uma reflexão acerca da humanização do cuidado e a atuação do SUS no âmbito do município de Aracaju - Freitas, Carlos Diêgo de Brito (2023)
With the sanction of Law No. 14,198/2021, patients hospitalized in health services, unable to receive visits and have contact with their family members, now have the regulated right to carry out virtual visits through video calls, thus guaranteeing a reception based on respect for fundamental rights and in the humanization of care. The focus of this research is on the differentiated view of hospitalized patients, considering their uniqueness, and the need to preserve humanized care. The research addresses the patient as a human being, holder of inalienable fundamental rights, defending the consolidation of a theoretical basis in favor of a new branch of Law, the Patient's Right. The paper analyzes whether the actions required by law nº. 14,198/2021 are adequate for the regulation of the National Hospital Care Policy of the Ministry of Health, and finally clarifies whether the Municipality of Aracaju has adopted effective actions to implement television as a form of humanized reception in favor of users assisted by public health services. This is a qualitative, explanatory and exploratory research, with interpretation of didactic material, legislation and news, searches in official databases and information provided by the Municipal Health Department of Aracaju, in addition to data collection through a questionnaire applied to the competent body for technical supervision of the care units that are the object of the research. In the end, it is concluded that television, despite being unanimously considered a method of qualified care and a tool for humanized reception, in its execution within the scope of hospital units linked to the SUS Aracaju, this has not yet fulfilled its purpose, being found the non-effectiveness of its regulatory law.